Preloved Luxury Bag Business Plan Through Social Media "Nalux Boutique" - Anissa Nabila Ramadhini; Suwandi (Jurnal Scientia, 2024)
The use of preloved luxury bags is in great demand among some consumers. Preloved's sales industry on social media is currently growing very rapidly. Nalux Boutique was founded in 2020 by starting to market through Instagram and it turns out that people's enthusiasm is very high. Nalux Boutique has an innovation to provide rentals for some of the luxury bags sold. The business strategy carried out by Nalux Boutique starts from analyzing STP (Segmentation, Targeting and Positioning) and analyzing the marketing mix strategy, as well as a SWOT analysis of the Nalux Boutique business. And pay attention to the risks that may occur during the course of running this business. The results of the strategy analysis found that this business focused on selling through online (Instagram social media) and based on the business feasibility analysis, it was stated that Nalux Boutique is feasible to run even though the Profitability Index is relatively small because the initial capital uses personal capital without using other loans and the profits are used to buy luxury bag stocks. The result of the payback period calculation is that the return of capital will occur in the 2nd year.